Location Based Service Untuk Informasi Sholat Jumat di Bandar Lampung: (Location Based Service for Friday Prayer Information in Bandar Lampung) (Talenta Conference Series: Science and Technology (ST), 2019)
Perkembangan teknologi informasi dan komunikasi mendorong berbagai perkembangan layanan yang mengikutinya.  Salah satunya adalah Location Based Service (LBS). Pada penelitian ini telah dikembangkan LBS yang ditujukan untuk memberikan informasi sholat jumat di Kota Bandar Lampung.  Informasi yang disajikan diantaranya adalah lokasi masjid, jadwal khotib jumat dan rute ke arah masjid dari posisi pengguna aplikasi. Aplikasi yang dikembangkan terdiri dari dua bagian, yaitu aplikasi berbasis web untuk pengeolaan data oleh adminisrator sistem dan aplikasi android  untuk pengguna. Komunikasi data antara dua aplikasi dilakukan memalui web service. Hasil pengujuian menunjukkan aplikasi yang dikembangkan dapat memberikan informasi yang dimaksud dan pengujian berdasar Black Box Equivalence Partitioning menunjukkan aplikasi berjalan sesuai dengan persyaratan yang ditetapkan.  The development in information technology on telecommunication aspect have changed people’s perception in using it. One of the telecommunication aspect is cellphone, which can be used as the tool in developing public service. Along with the development of science and technology, the new application is created, namely GPS (Global Positioning System). GPS can give Location Based Service (LBS), an information service which can be accessed by using smartphone through mobile network and is able to use geographic location. In this research, the researcher designs and creates an application which can give the information about the Friday prayer schedules in Bandar Lampung, including the information about mosques, preacher who is in charge in certain mosque, and shows the nearest mosque location within a radius of 1 km. The application consists of Android Mobile for users and also Web Based System for Administrator which is connected with Web Service technology. The conclusion of this study is that the new application has been successfully created and can give the information about Friday prayer in Bandar Lampung.  The test result by using Black-Box equivalence partitioning shows that the application runs comply with the requirement.
Keywords: Android; Black-Box; Equivalence Partitioning; Location Based Service (LBS); Friday prayer; web service